An ontology for sharing and managing information in disaster response: An illustrative case study of flood evacuation - Khantong, S. (Akademiai Kiado Rt., 2020)
Information management and sharing is an essential ingredient, but a difficult and challenging problem for disaster response management. This paper proposes an ontology as a model to organize and structure information in order to improve the information management and sharing in disaster response management. The ontology was designed and developed based on philosophically grounded foundational ontologies. It was also implemented in ontological languages and demonstrated and evaluated in a case study of the flood evacuation process. This paper also provides a systematic approach to develop a well-founded domain ontology that addresses both static and dynamic aspects of a given domain. Â© 2020 The Authors